2015
DOI: 10.1164/rccm.201407-1338oc
|View full text |Cite
|
Sign up to set email alerts
|

Do Patients of Subspecialist Physicians Benefit from Written Asthma Action Plans?

Abstract: Rationale: Asthma clinical guidelines suggest written asthma action plans are essential for improving self-management and outcomes.Objectives: To assess the efficacy of written instructions in the form of a written asthma action plan provided by subspecialist physicians as part of usual asthma care during office visits.Methods: A total of 407 children and adults with persistent asthma receiving first-time care in pulmonary and allergy practices at 4 urban medical centers were randomized to receive either writt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
37
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 31 publications
3
37
0
Order By: Relevance
“…In terms of management, the low use of written management plans reported in this study, despite their recommendation in guidelines, is consistent with previous findings [32]. This may reflect the debate about the extent of the benefits of written management plans [35] since these benefits were first presented in 2004 [36]. The proportion of physicians employing written plans in Germany recorded in our study (37%) is lower than published data from the German Disease Management Programme (DMP) evaluation would suggest [37].…”
Section: Discussionsupporting
confidence: 91%
“…In terms of management, the low use of written management plans reported in this study, despite their recommendation in guidelines, is consistent with previous findings [32]. This may reflect the debate about the extent of the benefits of written management plans [35] since these benefits were first presented in 2004 [36]. The proportion of physicians employing written plans in Germany recorded in our study (37%) is lower than published data from the German Disease Management Programme (DMP) evaluation would suggest [37].…”
Section: Discussionsupporting
confidence: 91%
“…[5][6][7][8] Only one study in 2005 by Agrawal et al showed that adding WAAP can improve asthma outcome when compared with controlled group. 4 Noticeably both Agrawal et al and our study, all of the children applied the peak flow-based asthma action plan but other studies partially applied symptom-based asthma action plan.…”
mentioning
confidence: 99%
“…A now rather old Cochrane review (published in 2006) concluded that symptom-based WAPs were more effective in reducing exacerbations compared to peak flow-based WAP;32 a trial published in 2004 demonstrated that peak flow monitoring was not effective in preventing attacks in children33 and peak flow monitoring is not routinely recommended for pediatric asthma management. A recent randomized control trial undertaken in ā€œsubspecialtyā€ practice in the US recruited adults and children and found no benefit of a WAP over no written instructions;34 it seems that the benefit from a WAP arises from more than simply having a handheld document to refer to when symptoms increase.…”
Section: Introductionmentioning
confidence: 99%